Exploring National Transportation Safety Board Aviation Modality Recommendations Through Content and Sentiment Analyses: 2015–2019 - Brian J. Roggow (Safety)
Aviation safety recommendations are the National Transportation Safety Board’s key mechanism for effecting improvements and curtailing subsequent accidents. Aviation safety recommendations and their associated correspondence have been minimally explored in the extant literature, potentially overlooking constrained versus successful risk mitigation themes. This research aimed to qualitatively explore 187 aviation safety recommendations using a framework adapted from the SHELL model. The research also examined the recommendations’ correspondence content to illuminate the characteristics typical of positive versus negative sentiments. The results included risk mitigation themes distributed across the categories of addressees, report statuses, and reiterations. Addressing company, management, manning, or regulatory issues was the most prevalent risk mitigation strategy, followed by physical environment and other human-system support mitigations. The sentiment analyses’ results included distributions across addressees, statuses, time, reiterations, and correspondences. NTSB and addressee correspondence sentiments remained mostly consistent over time and interactions, whereas differences were observed based on addressees and unacceptable report statuses. This article offers the first systematic analysis of NTSB aviation safety recommendations’ risk mitigation themes and addressee correspondences.